Formation of an organizational and economic mechanism for the greening of economic relations in the water use sector - Mahats, N. (Економічний вісник Донбасу, 2024)
Relevance of the study. In the context of modern environmental challenges, increasing requirements for rational environmental management, and the need to integrate environmental principles into the water use sector, the development of an effective organizational and economic mechanism for the greening of economic relations is of particular importance. The greening of water use is an important direction of the state policy of Ukraine in the context of adaptation to European standards of sustainable development, which involves introducing innovative technologies, increasing the environmental responsibility of business entities, and improving institutional support. In the war and post-war period, Ukraine will face large-scale challenges in restoring critical infrastructure, which requires the development of mechanisms that will contribute to the effective management of water resources and the ecological transformation of enterprises. Aim and objectives of the study. The study aims to substantiate the theoretical and methodological foundations and develop an organizational and economic mechanism for greening economic relations in the water use sector in Ukraine. The main objectives include: identifying key structural elements of the mechanism, studying the institutional, economic, and technological aspects of its functioning, and substantiating instruments for regulating and stimulating greening in the water use sector in Ukraine. Results. The essence of the concept of an organizational and economic mechanism for the greening of economic relations is determined as a set of organizational forms and economic levers aimed at integrating environmental principles into the practice of using water resources and ensuring the stimulation of environmental protection measures through improving the institutional basis, information and analytical support, technological modernization and financial and economic instruments to achieve the optimal balance between economic, environmental and social goals of water management development. It is determined that the institutional environment of water use in Ukraine requires harmonization with European environmental standards, which involves adapting the regulatory framework to the principles of the blue economy, institutional support for the formation of standards of social responsibility of business in the water sector and the implementation of water management restoration plans considering environmental principles into general projects of post-war economic recovery. The need for technological modernization aimed at the verification and reconstruction of water infrastructure by modern environmental standards, the development of closed cycles of water use, and blue-green infrastructure based on alternative sources of water supply is substantiated. The use of financial and economic levers is proposed financial instruments of "green" growth, mechanisms for market distribution of water resources, environmental insurance, and attraction of international investment resources to support environmental reforms. Conclusions. The implementation of the proposed mechanism will facilitate the transition from traditional resource-intensive models of water use to environmentally responsible economic relations and strengthen the integration of environmental principles into the water resources management system, ensuring the harmonization of economic and environmental interests. Its implementation will allow us to increase the efficiency of water resources use, stimulate enterprises to implement environmental technologies, strengthen institutional support for greening, and attract additional financial resources for the modernization of water infrastructure. The use of economic levers, in particular financial instruments for "green" growth, mechanisms for market allocation of water resources, and the attraction of international financial support, will contribute to ensuring the formation of appropriate conditions for the ecological transformation of the water sector of Ukraine. Актуальність. В умовах сучасних екологічних викликів, посилення вимог до раціонального природокористування та необхідності інтеграції природоохоронних принципів у сферу водокористування особливої значущості набуває розробка ефективного організаційно-економічного механізму екологізації економічних відносин. Екологізація водокористування є важливим напрямом державної політики України в контексті адаптації до європейських стандартів сталого розвитку, що передбачає впровадження інноваційних технологій, підвищення екологічної відповідальності суб’єктів господарювання та вдосконалення інституційної підтримки. У воєнний та повоєнний період Україна стикатиметься з масштабними викликами щодо відновлення критичної інфраструктури, що потребує розробки механізмів, які сприятимуть ефективному управлінню водними ресурсами та екологічній трансформації підприємств. Мета та завдання. Метою дослідження є обґрунтування теоретико-методичних засад та розробка організаційно-економічного механізму екологізації економічних відносин у сфері водокористування в Україні. До основних завдань належать: визначення ключових структурних елементів механізму, дослідження інституційних, економічних і технологічних аспектів його функціонування, обґрунтування інструментів регулювання та стимулювання екологізації у сфері водокористування України. Результати. Визначено сутність поняття організаційно-економічного механізму екологізації економічних відносин як сукупність організаційних форм та економічних важелів, спрямованих на інтеграцію екологічних принципів у практику використання водних ресурсів та забезпечення стимулювання природоохоронних заходів через удосконалення інститу¬ційного підґрунтя, інформаційно-аналітичного забезпечення, технологічну модернізацію та фінансово-економічні інстру¬менти для досягнення. Визначено, що інституційне середовище водокористування в Україні потребує гармонізації з європейськими екологічними стандартами, що передбачає адаптацію нормативно-правової бази до засад блакитної економіки, інституційну підтримку формування стандартів соціальної відповідальності бізнесу у водному секторі та впровадження планів відновлення водного господарства із врахування екологічних принципів у загальні проекти повоєнного відновлення економіки. Обґрунтовано необхідність технологічної модернізації, спрямованої на верифікацію та реконструк¬цію водної інфраструктури відповідно до сучасних екологічних стандартів, розвиток замкнутих циклів використання води та блакитно-зеленої інфраструктури на основі альтернативних джерел водопостачання. Запропоновано застосування фінансово-економічних важелів, зокрема фінансових інструментів «зеленого» зростання, механізмів ринкового розподілу водних ресурсів, екологічного страхування та залучення міжнародних інвестиційних ресурсів для підтримки екологічних реформ. Висновки. Реалізація запропонованого механізму сприятиме переходу від традиційних ресурсомістких моделей водокористування до екологічно відповідальних економічних відносин, посилить інтеграцію екологічних принципів у систему управління водними ресурсами, забезпечуючи гармонізацію економічних та екологічних інтересів. Його реалізація дозволить підвищити ефективність використання водних ресурсів, стимулювати підприємства до впровадження екологічних технологій, зміцнити інституційну підтримку екологізації та залучити додаткові фінансові ресурси для модернізації водної інфраструктури. Застосування економічних важелів, зокрема фінансових інструментів «зеленого» зростання, механізмів ринкового розподілу водних ресурсів та залучення міжнародної фінансової підтримки, сприятиме забезпеченню формування належних умов для екологічної трансформації водного сектора України.